2013
DOI: 10.1111/ddi.12104
|View full text |Cite
|
Sign up to set email alerts
|

Do protected areas represent species' optimal climatic conditions? A test usingIberian water beetles

Abstract: Aim To assess the effectiveness of protected area networks in representing the climatic niche of Iberian water beetle species.Location Iberian Peninsula. Methods We used distribution data from 133 endemic water beetle species in the Iberian Peninsula. Climatic potential distributions were estimated by applying a multidimensional-envelope procedure based on climatic data (both current and future) and observed occurrences. Mahalanobis distances were calculated to obtain continuous climatic suitability values wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 61 publications
3
29
0
Order By: Relevance
“…Likewise, high degrees of endemicity in current species distribution patterns are a result of in situ diversification through divergent selection or genetic drift, which are promoted by environmental heterogeneity, geographical isolation, and habitat stability (Sandel et al 2011). Taking these processes into consideration when designing protected area networks increases the likelihood that biodiversity will persist long-term, even in the face of land-use and climate change (Sa´nchez-Ferna´ndez et al 2013). The use of environmental factors to explain biodiversity patterns allows conservation planners to capture both ecological diversification and accumulation of taxa (Mittelbach et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, high degrees of endemicity in current species distribution patterns are a result of in situ diversification through divergent selection or genetic drift, which are promoted by environmental heterogeneity, geographical isolation, and habitat stability (Sandel et al 2011). Taking these processes into consideration when designing protected area networks increases the likelihood that biodiversity will persist long-term, even in the face of land-use and climate change (Sa´nchez-Ferna´ndez et al 2013). The use of environmental factors to explain biodiversity patterns allows conservation planners to capture both ecological diversification and accumulation of taxa (Mittelbach et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The consistency (or inconsistency) of the environmental factors that drive biodiversity patterns within a protected area and, more broadly, across the whole biogeographic region, may be used as a heuristic measure for evaluating process-based representativeness that contributes to improving the long-term effectiveness of conservation plans (Sa´nchez-Ferna´ndez et al 2013;Albuquerque and Beier 2015). In Japan, plant diversity patterns are correlated with a variety of environmental factors that are a proxy for ecological and historical (evolutionary) processes: for example, current climate and edaphic factors drive species sorting; paleoclimatic and geological stability promote species accumulation; and geographical isolation is related to allopatric speciation .…”
Section: Introductionmentioning
confidence: 99%
“…Sánchez‐Fernández et al . () focussed on water beetles and demonstrated that protected areas provide the basic climatic conditions suitable for many species, but that most were close to their tolerance limits, which might compromise long‐term persistence. Similar results have been reported for other areas in Europe (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng and Bonebrake 2017). Moreover, few conservation planning studies have focused on insects, as compared to other taxa (Wilson and Maclean 2011;Sánchez-Fernández et al 2013). Some studies have already stressed the lack of effectiveness of the European Natura 2000 reserve network in representing the invertebrate fauna in different countries (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure has been widely used in spatial animal ecology (e.g. Etherington et al 2009) and is considered an useful tool to estimate the environmental suitability area for a given species (Calenge et al 2008;Sánchez-Fernández et al 2013;Guareschi et al 2013). Thus the final representation of the potential distribution for E. iberica was a map with continuous favourability values within its potential distribution, which ranged from 0 (low suitability) to 100 (high suitability).…”
Section: Current Potential Distributionmentioning
confidence: 99%